On some limit theorems for the maximum of sums of independent random processes - Matsak, I. K. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We study conditions of weak convergence of maximum of sums of independent random processes in the space $L_p.$ We present a number of applications to asymptotic analysis of some $ω^2$-type statistics.